An Assist for Cognitive Diagnostics in Soccer: Two Valid Tasks Measuring Inhibition and Cognitive Flexibility in a Soccer-Specific Setting With a Soccer-Specific Motor Response - Musculus, Lisa; Lautenbach, Franziska; Knöbel, Simon; Reinhard, Martin Leo; Weigel, Peter; Gatzmaga, Nils; Borchert, Andy; Pelka, Maximilian (Frontiers in Psychology, 2022)
In professional soccer, players, coaches, and researchers alike recognize the importance of cognitive skills. Research addressing the relevance of cognitive skills has been based on the cognitive component skills approach (i.e., general cognitive processes) or the expert performance approach (i.e., sport-specific cognitive processes). Our project aimed to combine the strengths of both approaches to develop and validate cognitive tasks measuring inhibition and cognitive flexibility in a soccer-specific setting with a soccer-specific motor response. In the main study 77 elite youth soccer players completed a computerized version of the standard flanker and number–letter tasks as well as flanker and number–letter tasks requiring a soccer-specific motor response (i.e., pass) in a soccer-specific setting (i.e., the SoccerBot360). Results show good reliability for both tasks. For the SoccerBot360 number–letter task, switch effects for response times and accuracy and acceptable convergent validity were shown. A flanker effect for response time but not accuracy was apparent. Due to no acceptable convergent validity, the flanker task was revised (i.e., adaptation of stimuli) and 63 adult soccer players participated in a follow-up validation study in the SoccerBot100. The revised flanker task showed the flanker effect for response time, but not for accuracy. However acceptable convergent validity for response time was present. Thus, the soccer-specific number–letter and to some extent the soccer-specific flanker task show potential to be used as a valid cognitive diagnostic tool by soccer clubs.